Contribution of V.V. Salov to building of narrow-gauge railways of the Russian Empire (the second half of ХІХ century) - I. I. Sukhenko (History of science and technology, 2013)
It registers in the article, that a prominent engineer and railway administrator V.V. Salov did a ponderable contribution to building of narrow-gauge railways. He managed to prouve the necessity of narrow-gauge lines. As an active supporter of building of cheap railways of the facilitated type in a country, he, of course,was also advocated the construction of narrow-gauge railways. Back in the late of 60-ies of ХІХ century he began to put in reality the idea of their construction. The first among them was the Livenskaya narrow-gauge railway, which was built at the expence of the state treasury.